(untitled) (Sebha University Conference Proceedings, 2025)
This paper includes the creation of an integrated network consisting of two branches, where a network is designed and linked using virtual networks, monitored and analyzed using monitoring and analysis tools. The analysis results identify network errors and propose solutions, if possible- for example, a particular server stops, the user is unable to reach a certain destination within the network, the loss of transmitted data and not reaching the destination are some of the most common network errors that may occur within a network that lead to poor network service quality. VPN (Virtual private network) techniques have been used, which provide the creation of a protected network connection when using public networks, where they encrypt network traffic on the Internet and hide electronic identity, which makes tracking online activity and data theft very difficult. One of the monitoring techniques was used (Port Mirroring) where a copy of the traffic is sent to a separate port for monitoring and analysis to help detect network failures without affecting the traffic flow. This technique will improve network performance and save time and effort wasted in searching for the cause of the problem in the network. The results show the impact of using Port Mirroring and VPN techniques to improve the security of the network by analyzing access to the network and identifying potential issues before they occur , detecting malicious activities and protecting the data when it was transmitted over the Internet.